Tradisi Ngeyehin Karang Sebagai Praktik Ekoteologi Masyarakat Bali Aga - Ni Putu Ayu Heppyana; I Nyoman Suka Ardiyasa; Ni Luh Gede Hadriani (Jayapangus Press, 2026)
The tradition of Ngeyehin Karang in Pedawa Village represents a ritual practice of the Bali Aga community that integrates spirituality, social life, and ecological awareness. This study aims to examine the symbolic meaning, socio-religious function, and ecological contribution of the Ngeyehin Karang tradition in maintaining environmental balance and sustaining freshwater resources. This research employed a qualitative descriptive-narrative approach, with data collected through observation, in-depth interviews, and documentation. The findings show that Ngeyehin Karang functions not only as a purification rite for the household yard but also as an ecotheological practice that places nature within a sacred order. This tradition strengthens social solidarity through collective cooperation, serves as a medium for transmitting ecological values to younger generations, and shapes the community’s collective awareness in caring for land, water, and vegetation. These values are rooted in the philosophy of Tri Hita Karana, particularly the harmonious relationship between humans, the divine, and the environment. Therefore, Ngeyehin Karang can be understood as a model of environmental conservation based on local spirituality, which remains relevant in responding to contemporary ecological crises.